Africa Diary : News from the Continent - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2025)
Mauritius ordered all internet service providers to suspend access to social media platforms until a day after the 11 November general election, sparking such outrage from civil society groups that the government of the ruling Militant Socialist Movement (MSM) party was forced to overturn the ruling a day later. “National security” was the reason given by the office of the Prime Minister. As it turned out national security was not at risk. The main opposition party won a landslide victory, preserving an electoral practice of simply and seamlessly alternating power between two dynasties of family leaders since independence from Britain in 1968.